America's Racial Reckoning Within Perinatal Communication: A Rapid Review Using Sociotechnical Systems Theory to Compare Publications Before and After 2020 - Maren S.G. Henderson; Meghan M. JaKa; Jennifer M. Dinh; Barbara A. Olson-Bullis; Corinne Brown-Robinson; Thomas E. Kottke; Jeanette Y. Ziegenfuss (SAGE Publishing, 2023)
Perinatal communication is one factor driving racial disparities in maternal and infant morbidity. The murder of George Floyd in May 2020, in addition to the disproportionate impacts of the Covid-19 pandemic on communities of color, was a catalyst for American society to address racial injustices with a renewed sense of urgency. Drawing upon sociotechnical systems (STS) theory, this rapid review describes changes in the literature regarding the organizational, social, technical, and external subsystems that affect communication between perinatal providers and their Black patients. The goal of this work is to support health system optimization of health communication initiatives and, as a result, improve patient experience and parent and child outcomes. As part of a multi-year project designed to improve health communications about safe fish consumption during pregnancy, and in response to racial disparities among our health system's patient population related to receipt of nutrition messages during prenatal visits, we conducted a rapid review of literature on Black parents' experience of all communication while receiving perinatal care. A search of PubMed identified relevant articles published in English since 2000. Articles were screened to include articles that focused on Black people receiving perinatal care. Article content was then coded using deductive content analysis guided by STS theory to inform healthcare system improvement efforts. Differences in the prevalence of codes pre- and post-2020 are compared using chi-square statistics. The search in PubMed yielded 2419 articles. After screening, 172 articles were included in the rapid review. There was an increased recognition of communication as a key component of quality perinatal care after 2020 ( P  = .012) and of the limitations of standardized technical communication ( P  = .002) after 2020. Emerging literature suggests improving perinatal health communication and relationships with Black parents would address disparities in perinatal patient and baby outcomes. Healthcare systems must address the racial disparities in maternal and child outcomes. Since 2020, public attention and published research on this issue has increased. Understanding perinatal communication using STS theory aligns subsystems in service of racial justice.